THE MACHINE OIL DRAINER DESIGN IN SMALL MEDIUM-SIZE ENTERPRISES (SMEs) OF FOOD PROCESSING OF CASSAVA CHIPS IN CIAMIS DISTRICT - Riyaldi, Slamet; Setiawan, Tia (Universitas Muhammadiyah Jakarta, 2021)
Machine technology is currently playing an important part in supporting small and medium-sized enterprises (SMEs)' growth and continuity. Oil filtration in cassava chips that are fried in SMEs is also a concern as chips which are not durable, moldy, and poorly smelling. A machine oil drainer is therefore required to prevent this so that SMEs can compete internationally according to the target. Further to the above, the researcher would recommend the design of the oil drainer used by SMEs in the production of cassavas chips. The design uses a case study by SMEs. In addition, to find out productivity level, the comparison before and after the use of an oil drainer is measured at the beginning and the end of the study. A case study technique with the chosen sample, namely the processing of cassava chips in the Ciamis Regency, is the analysis tool used. As for the data source, it is obtained by data collection techniques using questionnaires, interviews, observation, and documentation exploration through primary and secondary data collection. It is understood from the outcomes of the above discussion that the Machine Oil Drainer plays a role in reducing the oil content of cassava chips, where it can work and operate efficiently. If it can make food durable, mold-free, and smell rancid with the System Oil Drainer, the consistency and efficiency of cassava chips are thus growing. The Research output is in the form of a Machine Oil Drainer that can assist in the filtering process to minimize the oil content of cassava chips in Ciamis Regency cassava chips SMEs.